PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL TERHADAP KUALITAS LAPORAN KEUANGAN - Rusdi Abdulkarim (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
This study aims to determine and analyze how much influence the implementation of accrual-based government accounting standards on the quality of reports. This research was conducted at the Regional Financial Management Agency of Pohuwato Regency by taking 42 employees as the research sample. Data collection techniques using questionnaires and using multiple regression as a method of data analysis. The results showed that the Accrual-Based Government Accounting Standards simultaneously had an effect on Report Quality by 98.5% and 1.5% was influenced by external variables that were not studied. Income-Lo (X1) is 25.1%, Expenses and Assets (X2) is 46.2%, Debt and Equity (X3) is 113.9%, LRA Revenue (X4) is 105.9%, Expenses (X5) ) amounting to 32.1% and Financing (X6) of 18.5% partially influence the Quality of Financial Statements (Y).